Lithium ion secondary battery negative electrode material as well as preparation method and application thereof
By designing an ordered zincblende or layered structure for the CuxGeSey anode material, the specific capacity and cycle stability issues of lithium-ion battery anode materials are solved, achieving high energy density and long lifespan lithium-ion battery performance and simplifying the material application process.
Patent Information
- Application Number
- CN202511092538.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-05
- Publication Date
- 2025-11-07
- Estimated Expiration
- 2045-08-05
Smart Images

Figure CN120914252A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of lithium ion secondary batteries, and relates to a lithium ion secondary battery negative electrode material and a preparation method and application thereof. BACKGROUND
[0002] A lithium ion battery is a secondary battery (a rechargeable battery), which mainly relies on the movement of lithium ions between the positive electrode and the negative electrode to work. During the charging and discharging process, lithium ions are embedded and de-embedded between the two electrodes: when charging, lithium ions are de-embedded from the positive electrode, embedded into the negative electrode through the electrolyte, and the negative electrode is in a lithium-rich state, and when discharging, the opposite is true.
[0003] With the rapid growth of demand for portable energy in the fields of electrical, electronic, automobile and aerospace, etc., the market has put forward higher requirements for the performance of lithium ion batteries, including high specific capacity, excellent cycle stability and high safety, etc. As the core component of lithium ion batteries, the performance of electrode materials directly determines the overall performance of the battery.
[0004] At present, the commercialized lithium ion battery negative electrode material mainly uses graphite, and its theoretical specific capacity is about 372mAh / g, which is difficult to meet the increasing demand for high energy density. Although silicon-based negative electrode materials have a high theoretical specific capacity (3579mAh / g), but during the charging and discharging process, the volume expansion rate exceeds 300%, which will cause the destruction of the electrode structure, and further cause the cycle performance to decay sharply, and even cause safety accidents, which seriously limits its practical application.
[0005] Therefore, it is necessary to provide a lithium ion secondary battery negative electrode material, which is applied to a lithium ion battery, so that the lithium ion battery has more excellent comprehensive performance, and the application scenarios of the negative electrode material are expanded. SUMMARY
[0006] In order to overcome the problems in the background art, the application utilizes the larger ion radius (1.98Å) of Se element in the negative electrode material to increase the bond length and weaken the crystal field effect, so that the negative electrode material forms an ordered zinc blende or layered structure. Among them, the ordered zinc blende structure has a natural three-dimensional lithium ion diffusion channel, which can significantly reduce the lithium ion migration resistance and improve the ion transport efficiency of the material, which is helpful to improve the rate performance and fast charging capacity; and the layered structure has good interlayer buffering effect, which can effectively absorb the volume change during the charging and discharging process, and improve the structural stability and cycle life. In addition, the Li2Se byproduct generated in the lithium intercalation / delithiation process of the material has high chemical stability, which can inhibit the side reaction between the material surface and the electrolyte to a certain extent, thereby improving the interface stability, enhancing the long-term cycle performance and practical application safety of the material.
[0007] In order to achieve the above purpose, the application realizes the technical scheme as follows: In one aspect, the present application provides a lithium ion secondary battery negative electrode material, which has a chemical formula of Cu x GeSe y wherein x and y represent the atomic ratio of Cu and Se in the stoichiometric proportion in the negative electrode material, and the range of x and y is 0.1≤x≤5, 0.1≤y≤5, and 0.02≤x / y≤5.
[0008] Preferably, the negative electrode material is in a powder form, and the particle size is 0.1 nm-500 μm.
[0009] In another aspect, the present application provides a preparation method of the above negative electrode material, which comprises the following steps: (1) Cu powder, Ge powder and Se powder are weighed according to the stoichiometric proportion and mixed to obtain a mixture; (2) the mixture obtained in step (1) is heated and kept warm under vacuum, and then cooled to room temperature with the furnace to obtain an ingot; (3) the ingot in step (2) is ground into powder, and the powder is used as raw material for discharge plasma sintering to obtain a lithium ion secondary battery negative electrode material.
[0010] Preferably, in step (2), the heating temperature is 1173 K, the holding time is 72 h, and the vacuum degree is 10 -4 Pa.
[0011] Preferably, in step (3), the discharge plasma sintering temperature is 648 K, the sintering pressure is 45 MPa, and the sintering time is 10 min.
[0012] The present application also provides an application of the above negative electrode material in a negative electrode sheet, which is composed of a current collector and an active material layer, and the active material layer covers the surface of the current collector and comprises a mixture of the lithium ion secondary battery negative electrode material and a binder. The current collector is selected from conventional current collectors in the art, such as copper foil current collector, and the binder is selected from conventional binders in the art, such as polyvinylidene fluoride (PVDF).
[0013] Preferably, in the active material layer, the mass ratio of the binder and the lithium ion secondary battery negative electrode material is negative electrode material: binder = 6-10: 1-5.
[0014] Preferably, the active material layer further comprises a conductive agent, and in the active material layer, the mass ratio of the lithium ion secondary battery negative electrode material, the binder and the conductive agent is negative electrode material: binder: conductive agent = 6-10: 1-5: 1-3. The conductive agent is selected from conventional conductive agents in the art, such as conductive carbon black.
[0015] As preferred, the thickness of the active material layer in the negative electrode sheet is 10-500 μm.
[0016] The application also provides the use of the above negative electrode sheet in the preparation of lithium ion secondary batteries.
[0017] The application finally provides the use of the above negative electrode material in the preparation of lithium ion secondary batteries.
[0018] The application has the following advantages: 1. The application significantly enhances the diffusion rate of lithium ions in the material by using a negative electrode material with an ordered zinc blende or layered structure, which helps to improve the rate performance and fast charging capability.
[0019] 2. The application uses Cu x GeSe y As a negative electrode material for lithium ion secondary batteries, the stable Li2Se protective layer is formed in situ at the electrode interface during the charging and discharging process, and its high stability reduces the probability of side reactions with the electrolyte, effectively inhibiting the occurrence of side reactions, thereby improving the interface stability of the negative electrode material. Good cycle performance and rate performance can be achieved without additional modification such as coating or doping of the negative electrode material, thereby simplifying the application process of the negative electrode material and reducing the cost of material application.
[0020] 3. The specific capacity of the negative electrode material of the application can reach more than 500 mAh / g, and the capacity retention rate can reach more than 90% after 1000h of conventional cycling, and the capacity retention rate can reach more than 80% after 1000h of high-rate (20C) cycling, and the volume expansion rate can be as low as 12%. The negative electrode material of the application has excellent comprehensive performance, and when used as a lithium ion secondary battery negative electrode material, the lithium ion secondary battery negative electrode material has excellent performance. BRIEF DESCRIPTION OF DRAWINGS
[0021] Figure 1 The performance test results of the negative electrode material of Example 1 are shown in the figure, wherein figure a is the rate performance of the negative electrode material, and figure b is the cycle stability of the negative electrode material. DETAILED DESCRIPTION
[0022] The application will be further described in detail below in conjunction with the drawings and specific examples, but the scope of protection of the application is not limited to the content described.
[0023] In the examples and comparative examples of the application, commercially available analytical pure reagents were used for experiments unless otherwise specified.
[0024] Example 1 The negative electrode material was prepared by the following method in this example: First, high-purity Cu powder (99.999%), Ge powder (99.99%), and Se powder (99.999%) were weighed and mixed according to stoichiometric ratios and then placed into a quartz tube; the quartz tube was then evacuated to a vacuum level of 10. -4 The ingot was then sealed; it was then slowly heated to 1173 K and held for 72 hours to ensure a complete reaction; subsequently, it was cooled to room temperature in the furnace. The resulting ingot was ground into fine powder and further sintered under vacuum conditions by spark plasma sintering (SPS) at 648 K and 45 MPa for 10 minutes to obtain a dense bulk material. The bulk material was then crushed and ground to obtain powdered anode material.
[0025] For ease of experimentation, this embodiment uses the negative electrode material to fabricate the negative electrode sheet, which is then used to fabricate a lithium-ion secondary battery. The specific fabrication process is as follows: (1) Preparation of negative electrode sheet: In this embodiment, Cu2GeSe3 powder with a particle size of 1μm was selected as the negative electrode material, and PVDF was selected as the binder. First, 80g of negative electrode material and 10g of binder powder were added to N-methylpyrrolidone (NMP) solvent and mixed evenly to obtain a solution. The amount of solvent was determined according to the actual dissolution situation, and it was determined that the negative electrode material and binder could be completely dissolved, or it could be in excess. The solution was coated on the surface of a copper foil current collector with a thickness of 12μm, and the coating amount was 10mg / cm. 2 Then, the copper foil current collector is vacuum dried to remove the solvent, resulting in a negative electrode with an active material layer thickness of 200 μm.
[0026] (2) Preparation of the positive electrode sheet: In this embodiment, conductive carbon black was selected as the conductive agent, PVDF as the binder, NMP as the solvent, and conventional positive electrode active material in the art was selected. In this embodiment, LiFePO4 was selected. First, 5g each of the conductive agent and the binder (accounting for 5% of the total mass of the positive electrode material) were weighed and added to 30 mL of NMP solvent, and stirred evenly to form a solution. Then, 90g of LiFePO4 powder (accounting for 90% of the total mass) was added, and stirring was continued to form a uniform slurry. The total mass of the obtained slurry was 100g, and the solid content was about 60%. The slurry was uniformly coated on an aluminum foil current collector with a thickness of 10μm and a coating amount of 20mg / cm². Then, it was dried in a vacuum drying oven at 80℃ to obtain the positive electrode sheet.
[0027] (3) Preparation of lithium ion battery: select a conventional separator in the art as the separator of the lithium ion battery, and a polyolefin microporous membrane is selected in this embodiment. A conventional electrolyte in the art is selected. In this embodiment, 1M LiPF6 / (EC+DEC, 1:1) commercial electrolyte is selected, which is composed of 1 mol / L lithium hexafluorophosphate (LiPF6) dissolved in a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1. The prepared positive electrode sheet, negative electrode sheet and separator are assembled in a conventional winding manner, and the tab is packaged with an aluminum plastic film to obtain a soft package type lithium ion battery.
[0028] Based on the soft package lithium ion battery prepared in this embodiment, the performance of the negative electrode material in the lithium ion battery is tested, and the results are shown in Figure 1
[0029] As can be seen from Figure 1 a, the negative electrode material of the application exhibits good rate performance at different rates, and still maintains a reversible capacity of about 270 mAh / g at a high current density of 3 A / g; when the current density is restored to 0.1 A / g, the capacity is almost completely restored, indicating that the material has excellent structural stability and reaction reversibility. As can be seen from Figure 1 b, the material can maintain a capacity retention rate of about 90% after 50 cycles at a current density of 0.5 A / g, exhibiting good cycle stability. In addition, the coulombic efficiency is always close to 100% during the entire rate test and cycle process, indicating that the material has few side reactions during the electrochemical reaction process, and has high reversibility and interface stability.
[0030] Example 2 In this embodiment, the same method as in Example 1 is used to prepare the lithium ion battery and the negative electrode material, and the difference is that in this embodiment, the negative electrode material is CuGeSe (x=1, y=1, x / y=1), the amount of the negative electrode material is 90 g, the mass of the binder is 10 g (mass ratio 9:1), the particle size of the negative electrode material is 0.1 nm, and the thickness of the active material layer is 10 μm.
[0031] The negative electrode material in this embodiment belongs to a typical layered structure material with x / y≈1 in the scope of the application, and has a certain van der Waals gap between the layers, which can buffer the volume change during the lithium ion insertion / extraction process and maintain the structural integrity. The volume expansion rate of the negative electrode material in this embodiment is less than 12% during the cycle process, the electrode structure is well maintained, the capacity is equivalent to that of Example 1, the rate performance is slightly lower than that of Example 1 but still meets the requirements of high rate operation, the overall interface stability and coulombic efficiency are excellent, and it is suitable for application scenarios with high requirements for long life.
[0032] Example 3 The lithium ion battery and the negative electrode material of the present example were prepared by the same method as that of Example 1, except that Cu 0.1 GeSe5 as the negative electrode material (x = 0.1, y = 5, x / y = 0.02), the mass ratio of the negative electrode material: binder: conductive agent was 6:1:1, the particle size of the negative electrode material was 500 μm, and the thickness of the active material layer was 500 μm.
[0033] In the negative electrode material of the present example, the Cu-Se electron conduction network in the material was not obvious due to the extremely low content of Cu, and the electronic conductivity was lower than that of Example 1; however, the proportion of Ge elements was relatively increased, the alloying reaction dominated the lithium storage process, and a relatively high capacity could be provided. The rate performance of the negative electrode material of the present example was slightly lower than that of Example 1, the initial capacity was maintained at more than 500 mAh / g, the cycle stability was basically controllable, the interface reaction was mild, and it was indicated that even under the condition of extremely low x, the negative electrode material of the present application still had good comprehensive performance.
[0034] Example 4 The lithium ion battery and the negative electrode material of the present example were prepared by the same method as that of Example 1, except that the negative electrode material of the present example was Cu5GeSe (x = 5, y = 1, x / y = 5), and the mass ratio of the negative electrode material: binder: conductive agent was 10:5:3.
[0035] In the negative electrode material of the present example, a large amount of copper-rich phase existed, which was helpful to build a continuous electron conduction network, thereby greatly improving the electronic conductivity and the rate performance. A relatively high reversible capacity could still be maintained under the condition of high-rate discharge (>10C), but due to the excessively high proportion of Cu phase, the lithium ion diffusion channel was reduced, resulting in a slightly lower capacity (about 480 mAh / g). In addition, the structure was slightly rigid during the lithium intercalation process, the volume expansion was slightly increased (about 15%), but the cycle stability was still maintained well, the interface SEI film was dense and uniform, and it was suitable for high-power demand scenarios.
[0036] Example 5 The lithium ion battery and the negative electrode material of the present example were prepared by the same method as that of Example 1, except that the negative electrode material of the present example was still Cu2GeSe4, and the mass ratio of the negative electrode material: binder was set to 8:3.
[0037] Due to the high electronic conductivity of the negative electrode material of the present example itself, and the effective electron channel formed by the three-dimensional structure, the overall rate performance was still excellent without the addition of conductive agent. The capacity was stable under the condition of conventional rate (0.1C~1C), and the capacity retention rate was slightly lower than that of the system containing conductive agent under the condition of 20C rate, but it was still higher than 70%, which indicated that the material could omit the use of conductive agent under certain conditions, which was helpful to simplify the preparation process and reduce the cost, and was suitable for practical scenarios requiring formula simplification.
[0038] Comparative Example The comparative example uses CuGe2P3 as the negative electrode material to prepare a lithium ion secondary battery, and other additives and preparation methods are the same as those in Example 1.
[0039] CuGe2P3 as a phosphorus-based material has certain advantages in electronic structure, high electronic conductivity, strong lithium ion diffusion capacity, and good rate performance, and is suitable for battery systems with certain requirements for power output.
[0040] However, from the perspective of comprehensive application, CuGe2P3 still has certain limitations in cycle stability and interface stability. On the one hand, the interface product formed during the lithium intercalation process of the material is prone to side reactions in the electrolyte, and the interface film is difficult to maintain stability, which may cause capacity decay; on the other hand, the structure lacks effective interlayer buffering mechanism, and electrode structure damage may occur after long-term use. In addition, the material usually needs to be surface modified by coating or doping to improve its interface adaptability and process stability, and the preparation process is relatively complex.
[0041] Compared with CuGe2P3, Cu X GeSe y The material has higher energy output capacity in unit volume, and exhibits better volume energy density advantage. This is mainly due to the high reversible capacity of the material itself and the relatively low crystal density. Under the same electrode volume or electrode thickness conditions, Cu X GeSe y The material can accommodate more active components and release more charges, thereby improving the energy storage level per unit volume. In addition, the negative electrode material of the present application does not need to be additionally surface coated or doped, and the electrode structure is simpler, which is beneficial to improve the compaction density and electrode loading, and further optimize the volume utilization. In terms of structure, the negative electrode material of the present application forms an ordered crystal structure by adjusting the Cu / Se ratio, provides a continuous channel for lithium ion migration, and has a certain buffering capacity, which helps to relieve the volume expansion and improve the cycle stability. The Li2Se interface product generated during the reaction process is stable, can form a dense and uniform interface film on the surface of the material, effectively inhibits side reactions, and enhances the interface stability and coulombic efficiency.
[0042] For convenience of comparison, the parameters of the negative electrode materials of the examples and the comparative example of the present application are summarized in Table 1.
[0043] Table 1 In summary, the Cu X GeSe yThe negative material has high capacity, good cycle performance, process adaptability and high volume energy density without relying on complex modification, is suitable for application scenarios with high requirements for battery light weight, small size and integration, and has good popularization and application potential.
Claims
1. A lithium ion secondary battery negative electrode material, characterized by: The chemical formula of the lithium ion battery negative electrode material is Cu x GeSe y wherein x and y respectively represent the atomic number ratio of Cu and Se elements in the stoichiometric proportion in the negative electrode material, and the range is: 0.1≤x≤5, 0.1≤y≤5, and 0.02≤x / y≤5.
2. The negative electrode material for a lithium ion secondary battery according to claim 1, wherein the carbon material is a carbon material having a graphite structure. The negative electrode material is in powder form, and has a particle size of 0.1 nm-500 μm.
3. The method of claim 1, wherein the method is characterized by: The preparation method comprises the following steps: (1) Cu powder, Ge powder and Se powder are weighed according to stoichiometric ratio and mixed to obtain a mixture; (2) the mixture obtained in step (1) is heated and kept warm under vacuum, and then cooled to room temperature with the furnace, to obtain an ingot; (3) the ingot in step (2) is ground into powder, and the powder is used as raw material to perform spark plasma sintering, to obtain a lithium ion secondary battery negative electrode material.
4. The method of claim 3, wherein: The heating temperature in the step (2) is 1173 K, the holding time is 72 h, and the vacuum degree is 10 -4 Pa; In step (3), the spark plasma sintering temperature is 648 K, the sintering pressure is 45 MPa, and the sintering time is 10 min.
5. Use of the negative electrode material of lithium ion secondary battery according to claim 1 or 2 in a negative electrode sheet, characterized in that: The negative electrode sheet is composed of a current collector and an active material layer, the active material layer covers the surface of the current collector, and the active material layer comprises a mixture of the lithium ion secondary battery negative electrode material and a binder.
6. Use according to claim 5, characterized in that: In the active material layer, the mass ratio of the binder and the lithium ion secondary battery negative electrode material is negative electrode material:binder=6-10:1-5.
7. Use according to claim 5, characterized in that: The active material layer further comprises a conductive agent, and in the active material layer, the mass ratio of the lithium ion secondary battery negative electrode material, the binder and the conductive agent is negative electrode material:binder:conductive agent=6-10:1-5:1-3.
8. Use according to claim 5, characterized in that: In the negative electrode sheet, the thickness of the active material layer is 10-500 μm.
9. Use of the negative electrode sheet of claim 5 in the production of a lithium ion secondary battery.
10. Use of the lithium ion secondary battery negative electrode material of claim 1 or 2 in the production of a lithium ion secondary battery.
Citation Information
Patent Citations
Negative electrode material for lithium rechargeable battery, method of manufacturing thereof, negative electrode for lithium rechargeable battery, and lithium rechargeable battery
CN102782915A
Polynary phosphorus silicon germanium copper negative electrode material with defects for secondary battery and preparation method
CN108373163A
Lithium ion battery negative electrode active material, preparation method thereof and lithium ion battery
CN111276692A
Anode active material for lithium ion secondary battery, anode using the same, and lithium ion secondary battery
JP2012178299A
Solid electrolyte material and solid-state battery made therewith
WO2018183365A1